2017
DOI: 10.1097/pas.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 Expression in Granulocytic Epithelial Lesions of Idiopathic Duct-centric Pancreatitis (Type 2 Autoimmune Pancreatitis)

Abstract: Type 2 autoimmune pancreatitis (type 2 AIP) develops in isolation or sometimes in association with ulcerative colitis. Its diagnosis requires the histologic confirmation of granulocytic epithelial lesions (GELs) with no diagnostic biomarker currently available. This study aimed to elucidate the tissue expression of cytokines and their diagnostic value in this condition. In quantitative polymerase chain reaction for multiple cytokines using tissue-derived mRNA, the expression level of interleukin (IL)-8 was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 20 publications
5
42
1
Order By: Relevance
“…The American Journal of Pathologyajp.amjpathol.org A recent study of cytokine expression in pancreatic tissue samples from patients with type 2 autoimmune pancreatitis 59 revealed almost undetectable levels of IL4, IL10, and TNFA mRNA, highlighting the immunologic differences between the two forms of autoimmune pancreatitis. 59 The expression of INFG mRNA was comparable between types 1 and 2 autoimmune pancreatitis, whereas higher expression of CXCL8 (alias IL-8) mRNA was observed in type 2 disease, 13-fold higher than type 1 disease. 59 On immunostaining, the major source of CXCL8 appeared to be neutrophils, T cells, and damaged duct/ductular epithelium (Figure 2).…”
Section: Autoimmune Pancreatitismentioning
confidence: 99%
“…The American Journal of Pathologyajp.amjpathol.org A recent study of cytokine expression in pancreatic tissue samples from patients with type 2 autoimmune pancreatitis 59 revealed almost undetectable levels of IL4, IL10, and TNFA mRNA, highlighting the immunologic differences between the two forms of autoimmune pancreatitis. 59 The expression of INFG mRNA was comparable between types 1 and 2 autoimmune pancreatitis, whereas higher expression of CXCL8 (alias IL-8) mRNA was observed in type 2 disease, 13-fold higher than type 1 disease. 59 On immunostaining, the major source of CXCL8 appeared to be neutrophils, T cells, and damaged duct/ductular epithelium (Figure 2).…”
Section: Autoimmune Pancreatitismentioning
confidence: 99%
“…6 We recently reported that IL-8 (CXCL8) was overexpressed in type 2 AIP. 8 This chemotactic factor for neutrophils was expressed in the duct/ductular epithelium (83% of patients) and infiltrating inflammatory cells (100%) of patients with type 2 AIP. The aberrant expression of IL-8 in the epithelium was only focally observed in type 1 AIP or peritumoral pancreatitis.…”
Section: Introductionmentioning
confidence: 97%
“…Double immunostaining also revealed that CD3‐positive T‐lymphocytes infiltrating in type 2 AIP expressed IL‐8, whereas CD3/IL‐8 double positive cells were not present in type 1 AIP or peritumoral pancreatitis. Although the diagnostic sensitivity of pancreatic biopsies for type 2 AIP was 50% based on the presence of GELs, it increased to more than 90% with IL‐8 immunostaining …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations